IMPACT OF E-MARKETING ON SOCIAL NETWORK USAGE - Khan, Amir Sajjad; Khan, Inam Ullah (Archives of Business Research, 2014)
This study attempts to analyze the impact of e-marketing on social networking usage. A questionnaire was distributed for data collection among universities students, employing simple linear regression analysis. This paper concludes that there is a significant relationship between e-marketing, personalization and social networking usage, while personalization is unable to mediate the relationship between e-marketing and social networking usage. The managers of social network should consider e-marketing and personalization as a competitive policy to improve its usage. The drawback of this study is that the sample size was small due to time shortage. Key words: E-marketing, Personalization, Social networks